SURVEI KEBERADAAN FORMALIN PADA TELUR AYAM RAS DI PASAR TRADISIONAL INDUK DAN PASAR MODERN KAWASAN KOTA SEMARANG - Yuniva Tri Lestari; Dwi Sutiningsih; Praba Ginanadjar (Jurnal Kesehatan Masyarakat (Undip), 2015)
Formaldehyde is a disinfectant. According to Minister Regulation No. 1168 / Menkes / Per / X / 1999, formalin is one of the food additives that were prohibited by the formula CH2O. In the world of chicken farming, formalin have contact as an additive in feed, litter maintain the quality of the chicken coop and the raw material egg incubator disinfectant. The purpose of this study was to survey the existence of formaldehyde residues in eggs in a traditional home market and the modern market. The study was observational with cross sectional approach. Samples were eggs were sold by traders in traditional home markets and modern market in Semarang City with a total sample of 97 eggs were thought to contain residual formaldehyde. Samples were taken by simple random sampling. Data analyzed were done descriptively by univariate analysis. The result of this research were total of 91 samples or 98.9% of 92 chicken egg samples from traditional home markets were negative formaldehyde, as well as the 100% of 5 chicken egg samples of the modern market. Positive formaldehyde in one sample of the traditional home markets, namely 15,835 ppm (mg / kg). The resultsindicatethattraderswereawareofformalin36.10% andformalinharmful tohealthas much as38.10%. Traderswhodidn’tperform the separationof eggswithmaterialsuspected containformalinat63.9%. It was nedded to socialization formalindangerto the merchant. Theyshouldkeepeggsina sealed containerandseparatethematerialcontaining formaldehyde. Peopleshouldaddinformationsafe foodconsumption.